2020
DOI: 10.3389/fphar.2019.01653
|View full text |Cite
|
Sign up to set email alerts
|

A Proteotranscriptomic-Based Computational Drug-Repositioning Method for Alzheimer’s Disease

Abstract: Numerous clinical trials of drug candidates for Alzheimer's disease (AD) have failed, and computational drug repositioning approaches using omics data have been proposed as effective alternative approaches to the discovery of drug candidates. However, little multiomics data is available for AD, due to limited availability of brain tissues. Even if omics data exist, systematic drug repurposing study for AD has suffered from lack of big data, insufficient clinical information, and difficulty in data integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 60 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…The risk factors of development for AD diagnosis are important, of which age is dominant ( Currais et al, 2019 ). As the population ages, the prevalence of AD is increasing ( Lee et al, 2019 ). Studies have shown that for people over 60, the incidence doubles per 6.3 years.…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors of development for AD diagnosis are important, of which age is dominant ( Currais et al, 2019 ). As the population ages, the prevalence of AD is increasing ( Lee et al, 2019 ). Studies have shown that for people over 60, the incidence doubles per 6.3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Here, based on these molecular characteristics and an efficient and widely used computational drug-genomic method 23 25 , we identified multiple drugs that may have the potential to convert a noninflamed environment into an inflamed tumor environment (Fig. 6a ).…”
Section: Resultsmentioning
confidence: 99%
“…This will allow a better prognostic classification of the patients and a better management of the probands and of their families, by the identification of the -at risk individuals. These genetic data, together with novel clues coming from other “omics” [ 90 , 91 , 92 ], will allow also the development of novel and even more personalized therapies for AD and FAD treatment.…”
Section: Discussionmentioning
confidence: 99%